Hubungan Penggunaan Earphone dengan Gangguan Pendengaran Pada Mahasiswa Angkatan 2022 Fakultas Kedokteran Universitas Prima Indonesia - Ara Safitri Arianti; Andika Zayani Tambunan; Gusbakti Rusip (Jurnal Impresi Indonesia, 2025)
This study aims to examine the relationship between earphone use and hearing impairment among 2022 cohort students of the Faculty of Medicine, Universitas Prima Indonesia. The research employed an analytical observational design with a cross-sectional approach. A total of 37 respondents were selected based on predetermined inclusion and exclusion criteria, including being an active 2022 cohort student, using earphones, and consenting to undergo a pure-tone audiometry test. Data were collected through questionnaires and audiometry examinations, then analyzed using SPSS with normality tests and presented in distribution tables. The results indicate that the majority of respondents were female (78.4%) within the age range of 20–22 years, with most using earphones 1–3 days per week, for 1–3 hours, and at an intensity level below 60%. Audiometric findings revealed that 89.2% of respondents had normal hearing, while 10.8% experienced mild sensorineural hearing loss. These findings suggest that although most respondents remain within the normal category, there is an indication of hearing impairment among students who excessively use earphones. Therefore, this study emphasizes the importance of awareness among students to maintain hearing health by limiting both the duration and volume of earphone usage.